Application of mirror reconstruction and 3D printing technology in the treatment of Sanders type IV calcaneal fractures - Liao, Xiong; Deng, Jianliang; You, Di (Frontiers in Surgery, 2025)
ObjectiveTo explore the clinical efficacy of an integrated workflow combining mirror reconstruction and 3D printing for Sanders type IV calcaneal fractures—a severely comminuted subtype with limited evidence-based solutions and to explore a new individualized and accurate method for the treatment of Sanders type IV calcaneal fractures.MethodsA retrospective analysis of the clinical data of 20 patients with Sanders type IV calcaneal fractures who were treated with mirror image reconstruction and 3D printing technology in the Department of Orthopedics of our hospital from April 2021 to July 2023 was performed. There were 16 males and 4 females; their ages ranged from 38 to 62 years, with an average of 48.00 ± 1.84 years. All patients underwent clinical and radiological evaluation. The operation time, intraoperative blood loss, fracture healing time, and surgical complications were recorded. The width and height of the calcaneus, Böhler angle, and gissane angle were measured and compared before surgery, after surgery, and at the last follow-up. At the final follow-up, the American Orthopedic Foot and Ankle Society (AOFAS) ankle and hindfoot scores were used to evaluate hindfoot function, and the pain visual analog scale (VAS) was used to evaluate pain.ResultsAll 20 patients in this group underwent successful operations. The operation time ranged from 52 to 75 min, with an average of 59.55 ± 1.52 min. The volume of intraoperative blood loss ranged from 35 to 50 ml, with an average of 41.00 ± 1.16 ml. All patients received satisfactory follow-up, with follow-up times ranging from 12 to 38 months and an average of 16.55 ± 1.34 months. All the fractures healed, and the healing time ranged from 10 to 13 weeks, with an average of 11.55 ± 0.211 weeks. Two patients developed symptoms of sural nerve injury after surgery, two patients developed subtalar joint stiffness after surgery, and two patients developed traumatic arthritis changes in the calcaneellar joint during the 1-year follow-up. At the final follow-up, the calcaneal length, width, height, Böhler angle, and Gissane angle were significantly greater than those before surgery (p < 0.05). At the last follow-up, the AOFAS score ranged from 70 to 100 points, with an average of 88.15 ± 2.04 points, of which 8 cases were excellent, 10 were good, and 2 were fair, with an excellent and good rating of 90%. The VAS score ranged from 0 to 3 points, with an average of 0.95 ± 0.22 points.ConclusionThis integrated approach enables precise reduction with superior short-term outcomes, though long-term validation requires RCTs.